Alcohol Use Disorder in Southwestern and Northern Uganda: Prevalence and associated factors - Abraham Muhwezi; Tom Murungi; Pius Musinguzi; Davis Akampumuza; Mary Samantha; Moses Ocan; Henry Ochola; Godfrey Zari Rukundo; Samuel Maling; Edith K. Wakida; Celestino Obua (PLOS Global Public Health, 2026)
Alcohol use disorder (AUD) among adults is a major public health concern globally. Alcohol use disorder affects livelihood and contributes to adverse health outcomes. We investigated the prevalence of AUD and associated factors among adults (≥ 18years) in Lira and Isingiro districts in Uganda. This was a cross-sectional study conducted among adults (≥18 years) in households, selected using multistage sampling. Data were collected using an interviewer-administered questionnaire and the Alcohol Use Disorder Identification Test (AUDIT) tool. Data were downloaded from the Kobo Toolbox interface into Microsoft Excel and then exported to STATA version 17 for cleaning and analysis. A total AUDIT score of eight or more was used to define AUD. Binary Logistic regression was used to analyze factors independently associated with AUD at a 95% confidence level. A total of 577 participants were recruited in the study, with a median age of 35 years (IQR: 26–46). Half, 50.8% (293/577) of the participants were male. Over a third, 39.9% (230/577) of the participants had AUD. Factors significantly associated with AUD were; being male (aOR = 8.01; 95% CI: 5.02–12.76), age group of 31–50 years (aOR = 2.00; 95% CI: 1.21–3.33), secondary level education (aOR = 0.63; 95% CI: 0.21–0.78), having family members who use alcohol (aOR = 4.09; 95% CI: 2.54–6.59), use of other substances (aOR = 1.79; 95% CI: 1.10–2.92), and presence of major stressors (aOR = 3.58; 95% CI: 2.22–5.78). Alcohol use disorder was highly prevalent among adults in Uganda. Being male, age, use of other substances of abuse, and alcohol use among family members were significantly associated with AUD. The Ministry of Health and other key stakeholders should prioritize AUD, strengthen the regulation of alcohol use in the country, and provide rehabilitation for individuals with AUD.
Keywords: Alcohol use disorder; Uganda; Family members